Web Technology For Designing Online Learning Systems - Muslim; Badawi, Afif; Pramuja, Sigit (Cattleya Darmaya Fortuna, 2024)
The rapid advancement of web technologies has significantly transformed the educational landscape, necessitating the development of effective online learning systems. However, many existing platforms struggle to meet diverse learning needs, adapt to various teaching methodologies, and ensure user engagement. The problem addressed in this research is the lack of comprehensive online learning systems that effectively integrate modern web technologies to enhance educational outcomes. The primary goal of this research is to design and develop an online learning system that leverages cutting-edge web technologies to provide a flexible, interactive, and user-friendly educational environment. This system aims to support diverse learning styles, facilitate collaboration, and improve accessibility for both educators and learners. A mixed-method approach was employed in this study. The design and development of the online learning system were guided by user-centered design principles, involving iterative prototyping and testing. Quantitative data were collected through surveys to assess user satisfaction and system usability, while qualitative data were gathered from interviews to gain deeper insights into user experiences. The system's architecture was based on modern web technologies, including HTML5, CSS3, JavaScript frameworks, and cloud-based services. The research resulted in the successful development of an online learning system that received positive feedback from users for its intuitive interface and interactive features. Quantitative analysis indicated high levels of user satisfaction, while qualitative feedback highlighted the system's adaptability to different learning styles and its potential to enhance engagement. The integration of web technologies enabled real-time collaboration, seamless access to resources, and a personalized learning experience.